Legal Aid Institutions as a State Solution for the Poor in Getting Legal Protection - Rochman, Auliya (Faculty of Law, Universitas Negeri Semarang, 2020)
This study examines how the rules of the Legal Aid Institute in providing legal protection to the poor in Indonesia. As well as how the implementation of legal aid institutions in Indonesia in providing legal protection to the poor to examine the problem, the research methods used are; normative legal research methods with the statute approach, and the conceptual approach. The legal material collection technique used in this research is literature study. Research results confirm that poverty is one of the biggest problems in upholding human rights in obtaining legal assistance. The human rights approach is one of the basic principles of the government in serving people who are unable to overcome or provide legal protection in facing legal problems that are being faced either criminal, civil or state administration, so that the rights of the poor are not lost. Implementation of Providing Legal Aid is a law of social justice, where these values ​​include respecting the dignity and rights of individuals before the law, addressing the imbalance of power and legal injustice between the rich and the poor